U.S. national water and energy land dataset for integrated multisector dynamics research - Jillian Sturtevant; Ryan A. McManamay; Christopher R. DeRolph (Scientific Data, 2022)
Measurement(s) land use of renewable and nonrenewable technologies Technology Type(s) Esri Arcmap Sample Characteristic - Environment terrestrial; • aquatic Sample Characteristic - Location United States